Adult glioma imaging - Leben, Ana; Šurlan Popović, Katarina (Onkologija : Slovenian Journal of Oncology, 2019)
Gliomas are the most commonly occurring primary brain tumours. Since recent introduction of new guidelines we distinguish between different types of primary brain tumours on the basis of molecular markers which can provide important information for personalized treatment. Tumour identification can be either invasive (biopsy based) or non-invasive. The latter has recently been getting more recognition due to development of radiogenomics, which studies the connection between tumour imaging phenotypes and genomics. Magnetic resonance imaging, which uses many standard and nonstandard sequences, can serve as non-invasive identification method for tumour genotypes based on their specific morphological features. After having overviewed the existing literature about the topic, the authors of the article have assessed the imaging features of three tumour genotypes: isocitrate dehydrogenase mutation, 1p19q codeletion and methylguanine methytransferase promoter methylation. Despite the fast development of radiogenomics, there is still lack of comprehensive studies with standardized and sufficient patient samples to present more reliable results.